ML Flow serological test: complementary tool in leprosy - Janaína Olher Martins Montanha; Susilene Maria Tonelli Nardi; Fernanda Modesto Tolentino Binhardi; Heloisa da Silveira Paro Pedro; Milena Polotto de Santi; Vânia Del Arco Paschoal (Sociedade Brasileira de Dermatologia, 2023)
Abstract Background The evaluation of household contacts of leprosy cases allows the early diagnosis of new cases. Objective To associate the results of the ML Flow test with the clinical characteristics of leprosy cases and to verify their positivity in household contacts, in addition to describing the epidemiological profile of both. Methods Prospective study with patients diagnosed over the course of one year (n = 26), without prior treatment, and their household contacts (n = 44) in six municipalities in northwestern São Paulo, Brazil. Results There was a predominance of men among the leprosy cases, of 61.5% (16/26); 77% (20/26) were over 35 years old; 86.4% (22/26) were multibacillary; 61.5% (16/26) had a positive bacilloscopy; and 65.4% (17/26) had no physical disability. The ML Flow test was positive in 53.8% (14/26) of the leprosy cases and was associated with those who had a positive bacilloscopy and were diagnosed as multibacillary (p-value <0.05). Among the household contacts, 52.3% (23/44) were women and aged over 35 years; 81.8% (36/44) had been vaccinated with BCG ‒ Bacillus Calmette-Guérin. The ML Flow test was positive in 27.3% (12/44) of household contacts, all of whom lived with multibacillary cases; seven lived with positive bacilloscopy cases and six with consanguineous cases. Study limitations Difficulty in convincing the contacts to undergo the evaluation and collection of the clinical sample. Conclusion The ML Flow test, when positive in household contacts, can help the identification of cases that require more attention by the health team, as it indicates a predisposition to disease development, especially when they are household contacts of multibacillary cases, with positive bacilloscopy and consanguineous. The ML Flow test also helps in the correct clinical classification of the leprosy cases.